Hybrid Images Compression and Transmitted Using MC-CDMA System - Rajab , Maha A.; Al-Khafaji , Ghadah; A , Ahmed I. (Iraqi Journal of Science, 2022)
In this paper, the combined source coding with Multi Carrier Code Division Multiple Access (MC-CDMA) system is proposed, where the transmission of the compressed image produced from source coding through Additive White Gaussian Noise (AWGN) channel for a single user and multi users. In which the (MC-CDMA) system removes Inter Symbol Interference (ISI) and Inter Carrier Interference (ICI). The hybrid compression system of Discrete Cosine Transform (DCT) and predictive coding (PC) technique are integrated as a source coding. The simulation results indicates that the transmission system of a single user was much better than the transmission system of multi users. When the number of users increased, the Bit Error Rate (BER) increased. For a single user the BER =8.5×10-7 while the BER=3×10-6 for multi users. Signal to Noise Ratio (SNR) value is used to measure the performance of the MC-CDMA system , when SNR increased thus, BER decreased and preserve image quality and vice versa. Simulation results show that the BER=8×10-2 at SNR=0dB for block size (4×4) and (8×8), when SNR increase the BER decrease as in SNR=10dB the BER=8.5×10-7 for block size (4×4) and BER=4×10-7 for the block size (8×8).